2018
DOI: 10.11646/zootaxa.4450.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Aphaenogaster gamagumayaa sp. nov.: the first troglobiotic ant from Japan (Hymenoptera: Formicidae: Myrmicinae)

Abstract: Aphaenogaster gamagumayaa sp. nov., a new troglobiotic (true cave-dwelling) ant species, from a limestone cave on the island of Okinawa (Okinawa-jima), Ryukyu Archipelago, Japan is described. This is the first discovery of a troglobiotic ant in Japan and the second verified record worldwide. This species has only been found in a cave area with heavy guano deposits, and some worker ants were observed carrying guano. The evidence for categorizing this new species as troglobiont is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…While sequencing all the species from these two groups stands as an important objective for further research, phylogenetic results revealed a very interesting relationship between the two groups: the 'cecconii-like' and the 'splendida-like' morphologies each evolved independently two or three times, and at least twice 'cecconii-like' species were sisters to 'splendida-like' species. It is possible that the peculiar 'cecconii-like' morphology represents a form of adaptation to the light-avoiding or troglobiotic lifestyle that characterizes the species of this group, since similar traits are exhibited by other troglobiotic Palearctic species, such as the Japanese A. gamagumayaa Naka andMaruyama, 2018 (Borowiec andSalata 2014;Salata and Borowiec 2016;Naka and Maruyama 2018). Notably, the 'splendida-like' morphology is also, albeit to a lesser degree, associated with avoidance of sunlight by the slow-moving foraging workers, accomplished by either living in shady and humid environments or foraging at dusk or nocturnally (Salata et al 2021), and some species formerly assigned to the splendida group show somewhat intermediate characteristics between the two morphotypes.…”
Section: Discussionmentioning
confidence: 99%
“…While sequencing all the species from these two groups stands as an important objective for further research, phylogenetic results revealed a very interesting relationship between the two groups: the 'cecconii-like' and the 'splendida-like' morphologies each evolved independently two or three times, and at least twice 'cecconii-like' species were sisters to 'splendida-like' species. It is possible that the peculiar 'cecconii-like' morphology represents a form of adaptation to the light-avoiding or troglobiotic lifestyle that characterizes the species of this group, since similar traits are exhibited by other troglobiotic Palearctic species, such as the Japanese A. gamagumayaa Naka andMaruyama, 2018 (Borowiec andSalata 2014;Salata and Borowiec 2016;Naka and Maruyama 2018). Notably, the 'splendida-like' morphology is also, albeit to a lesser degree, associated with avoidance of sunlight by the slow-moving foraging workers, accomplished by either living in shady and humid environments or foraging at dusk or nocturnally (Salata et al 2021), and some species formerly assigned to the splendida group show somewhat intermediate characteristics between the two morphotypes.…”
Section: Discussionmentioning
confidence: 99%
“…n. are suggestive of non-troglomorphic characters. Generally, true cave-adapted characters or troglomorphy of ants are defined by 1) the elongation of appendages, 2) reduction of pigment, 3) reduction to loss of eyes, and 4) loss ability to fly (see discussion in Roncin & Deharveng, 2003;Naka & Maruyama, 2018). Carebara panhai sp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies related to the myrmecofauna from Brazilian caves (Ferreira, 2000;Dáttilo et al, 2010;Dáttilo et al, 2012) and in the world (Wilson, 1962;Tinaut & Lopez, 2001;Roncin & Deharveng, 2003;Moulds, 2006;Batucan & Nuñeza, 2013;Figueras & Nuňeza, 2013;Wynne & Voyles, 2013;Dejean et al, 2015;Pape, 2016;Naka & Maruyama, 2018) are limited regarding ant ecological function in the subterranean environment (Table 4). Ants usually are not target species for ecological studies in caves, as are other invertebrate groups -e.g., amphipods, cave salamander, copepods, beetles, isopods and spiders, as highlighted in a recent study surveyed by Mammola (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The first is a Ponerine ant, Leptogenys khammouanensis Rocin & Deharveng, 2003from Laos (Rocin & Deharveng, 2003. The second species was recently discovered and described, is a Myrmicinae ant, Aphaenogaster gamagumayaa Naka & Maruyama, 2018 found in Japan (Naka & Maruyama, 2018).…”
Section: Cavity Ant Richness Composition and Distribution Patternsmentioning
confidence: 99%
See 1 more Smart Citation